Apoptosis of THP-1 derived macrophages induced by sonodynamic therapy using a new sonosensitizer hydroxyl acetylated curcumin. - Longbin Zheng; Xinyong Sun; Xing Zhu; Fengxiang Lv; Zhaoyu Zhong; Feng Zhang; Wenhui Guo; Wenwu Cao; Liming Yang; Ye Tian (PLoS ONE)
Curcumin is extracted from the rhizomes of the traditional Chinese herb Curcuma longa. Our previous study indicated curcumin was able to function as a sonosensitizer. Hydroxyl acylated curcumin was synthesized from curcumin to eliminate the unstable hydroxy perssad in our group. The potential use of Hydroxyl acylated curcumin as a sonosensitizer for sonodynamic therapy (SDT) requires further exploration. This study investigated the sonodynamic effect of Hydroxyl acylated curcumin on THP-1 macrophage. THP-1 macrophages were cultured with Hydroxyl acylated curcumin at a concentration of 5.0 μg/mL for 4 hours and then exposed to pulse ultrasound irradiation (0.5 W/cm2 with 1.0 MHz ) for 5 min, 10 min and 15 min. Six hours later, cell viability decreased significantly by CCK-8 assay. After ultrasound irradiation, the ratio of apoptosis and necrosis in SDT group was higher than that in control, Hydroxyl acylated curcumin alone and ultrasound alone. Moreover, the apoptotic rate was higher than necrotic rate with the flow cytometry analysis. Furthermore, Hydroxyl acylated curcumin-SDT induced reactive oxygen species (ROS) generation in THP-1 macrophages immediately after the ultrasound treatment while ROS generation was reduced significantly with the scavenger of singlet oxygen Sodium azide (NaN3). Hydroxyl acylated curcumin-SDT led to a conspicuous loss of mitochondrial membrane potential (MMP) compared with other groups, while MMP was increased significantly with the scavenger of singlet oxygen Sodium azide (NaN3), ROS inhibitor N-acetyl cysteine (NAC) and Mitochondrial Permeability Transition Pore (MPTP) inhibitor Cyclosporin A (CsA). The cytochrome C, cleaved-Caspase-9, cleaved-Caspase-3 and cleaved-PARP upregulated after SDT through Western blotting. These findings suggested that Hydroxyl acylated curcumin under low-intensity ultrasound had sonodynamic effect on THP-1 macrophages via generation of intracellular singlet oxygen and mitochondria-caspase signaling pathway, indicating that Hydroxyl acylated curcumin could be used as a novel sonosensitizer in SDT for atherosclerosis.